2002
DOI: 10.1007/s00418-001-0376-9
|View full text |Cite
|
Sign up to set email alerts
|

RANK ligand, RANK, and OPG expression in type II collagen-induced arthritis mouse

Abstract: Rheumatoid arthritis (RA) is a systemic disorder characterized by synovial inflammation and subsequent destruction and deformity of synovial joints. The articular lesions start with synovitis, focal erosion of unmineralized cartilage, and then culminate in the destruction of subarticular bone by pannus tissue. Periarticular osteopenia and systemic osteoporosis follow as late complications of RA. Osteoclasts, specialized cells that resorb bone, play a central role in developing these osteolytic lesions. To eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Although cartilage loss was also reduced by OPG, the effects on cartilage were again lower than those on bone (48). Similar to this rat model, it has been recently suggested that the RANKL-RANK system plays an important role in osteoclastogenesis in both local and systemic osteolytic lesions in autoimmune type II collagen-induced arthritis in mice (49). These studies provide evidence for the role of osteoclasts (and of RANKL) in the pathogenesis of bone erosion in arthritis in several animal models of arthritis with distinct pathogenetic mechanisms.…”
Section: Rankl and Arthritissupporting
confidence: 71%
“…Although cartilage loss was also reduced by OPG, the effects on cartilage were again lower than those on bone (48). Similar to this rat model, it has been recently suggested that the RANKL-RANK system plays an important role in osteoclastogenesis in both local and systemic osteolytic lesions in autoimmune type II collagen-induced arthritis in mice (49). These studies provide evidence for the role of osteoclasts (and of RANKL) in the pathogenesis of bone erosion in arthritis in several animal models of arthritis with distinct pathogenetic mechanisms.…”
Section: Rankl and Arthritissupporting
confidence: 71%
“…Similarly, in type II collagen-induced arthritis in mice, RANK/RANKL plays an important role in osteoclastogenesis in local and systemic osteolytic lesions (64). This process may be driven by human RA inflammatory cells that express RANKL, whereas OPG is not detectable in the same setting (18).…”
Section: Animal Modelsmentioning
confidence: 99%
“…Increased osteoclast activity has been reported in many osteopenic disorders, including postmenopausal osteoporosis, Paget's disease, bone metastases, and rheumatoid arthritis (5)(6)(7). TRANCE interacts with two receptors: a secreted decoy receptor osteoprotegerin, OPG (8), and a transmembrane receptor, RANK (9 -11).…”
Section: Trancementioning
confidence: 99%